The Upsides and Downsides of the Dark Side: A Longitudinal Study Into the Role of Prosocial and Antisocial Strategies in Close Friendship Formation - Ciarrochi, Joseph; Sahdra, Baljinder K.; Hawley, Patricia H.; Devine, Emma K. (Frontiers in Psychology, 2019)
Resource control theory (RCT) posits that both antisocial and prosocial behaviors combine in unique ways to control resources such as friendships. We assessed students (N = 2803; 49.7 % male) yearly from junior (grades 8 to 10) to senior high school (11 to 12) on antisocial (A) prosocial (P) behavior, peer nominated friendship, and well-being. Non-parametric cluster analyses of the joint trajectories of A and P identified four stable profiles: non-strategic (moderately low A and P), bi-strategic (moderately high on A and P), prosocial (moderately low A and moderately high on P), and antisocial (moderately low on P, and very high on A). There were clear benefits to youth using bi-strategic strategies in junior high: They attracted relatively high levels of opposite-sex friendship nominations. However, this benefit disappeared in senior high. There were also clear costs: Bi-strategic youth experienced relatively low well-being, and this effect was significantly more pronounced for females than males. Prosocial youth were the only ones who maintained both high friendship numbers and high well-being throughout high school. We discuss the cost/benefit trade-offs of different resource control strategies.